2006
DOI: 10.1159/000098259
|View full text |Cite
|
Sign up to set email alerts
|

Two-Photon Microscopy of Vital Murine Elastic and Muscular Arteries

Abstract: Understanding vascular pathologies requires insight in the structure and function, and, hence, an imaging technique combining subcellular resolution, large penetration depth, and optical sectioning. We evaluated the applicability of two-photon laser-scanning microscopy (TPLSM) in large elastic and small muscular arteries under physiological conditions. Elastic (carotid) and muscular (uterine, mesenteric) arteries of C57BL/6 mice were mounted in a perfusion chamber. TPLSM was used to assess the viability of art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
102
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(107 citation statements)
references
References 71 publications
4
102
0
1
Order By: Relevance
“…Previous studies have demonstrated that the vessel, including the endothelial and smooth muscle cells, remains intact. 17,30 Whole blood was diluted with isotonic citrate buffer to adjust the platelet count to 1×10 8 platelets/mL blood. Before perfusion, the endothelium was labeled with anti-CD31-eFluor 450 antibody for 30 minutes.…”
Section: Ex Vivo Adhesion Assaymentioning
confidence: 99%
“…Previous studies have demonstrated that the vessel, including the endothelial and smooth muscle cells, remains intact. 17,30 Whole blood was diluted with isotonic citrate buffer to adjust the platelet count to 1×10 8 platelets/mL blood. Before perfusion, the endothelium was labeled with anti-CD31-eFluor 450 antibody for 30 minutes.…”
Section: Ex Vivo Adhesion Assaymentioning
confidence: 99%
“…DAPI was used to stain and image nuclei and was excited with a multi-photon laser at 720 nm (43). Collagen was imaged using a multi-photon laser at 850 nM via second-harmonic image, a scattering nonlinear process that requires no staining (30). Images were processed, and all channels were quantified to determine the total volume (number of expressed voxels) occupied by vascular smooth muscle cell (VSMC) nuclei, elastin, actin (within the media), and collagen with an in-house MATLAB algorithm available upon request.…”
Section: Animalsmentioning
confidence: 99%
“…There have been many different approaches used in preparing vessels for ex vivo microscopy reported in the literature. Some have included mounting variably sized vessel segments into a perfusion chamber (Megens et al 2007a;Megens et al 2007b), fresh and/or formalinfixed tissue preparations mounted between a glass slide and a coverslip (Kwon et al 2008;Lee et al 2009;Kim et al 2010, Lim et al 2010, Lim et al 2011Suhalim et al 2012), as well as agar gel-infused vascular casts that are segmented into thinly sliced molds and mounted on a glass slide (van Zandvoort et al 2004;Megens et al 2007a;Megens et al 2008;Le et al 2010). In vivo approaches have also been described but these are with the addition of mechanical techniques to help minimize motion artifact.…”
Section: Discussionmentioning
confidence: 99%